(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the efficacy and safety of Rezūm therapy through the first three clinical cases, with a discussion on the role of Rezūm compared to transurethral resection of the prostate in the current management of benign prostatic hyperplasia. Methods: A descriptive study of three benign prostatic hyperplasia cases treated with Rezūm therapy, including patient selection criteria, procedural technique, and pre- and post-treatment assessments: international prostate symptom score, quality of life score, post-void residual urine volume, prostate size reduction, complications, and sexual function. Results: After 3 months of follow-up, all three patients showed significant improvements: international prostate symptom score decreased by 77.8-80%, quality of life improved by 80%, and post-void residual was markedly reduced. Prostate volume decreased on both ultrasound and magnetic resonance imaging after 3 months. The duration of indwelling urinary catheterization ranged from 10 to 14 days. No procedure-related complications were reported. Sexual function was preserved in two patients, the remaining case could not be evaluated due to pre-existing erectile dysfunction. Conclu Rezūm, benign prostatic hyperplasia, LUTS, TURP. sion: Rezūm therapy is a safe, effective, and minimally invasive treatment option for patients with lower urinary tract symptoms/benign prostatic hyperplasia, with the notable advantages of preserving sexual function and enabling rapid recovery. It may serve as a suitable alternative to transurethral resection of the prostate in appropriately selected cases.